APLIKASI E-COMMERCE BERBASIS WEB MENGGUNAKAN METODE WEIGHTED MOVING AVERAGE DAN K-MEDOIDS - Arthian Terry Sammatha Sudarthio; Bagus Mulyawan; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Sugi Jaya Mandiri, Ltd. is a company specializing in sales of industrial equipments, such as cables, pipes, construction materials, machine spareparts et cetera. The company processes data manually by using Microsoft Excel. The process complicates data recapitulation, especially concerning large amounts of data. Another issue is the lack of advertising towards customer. This application aims to solve the problems by implementing data processing feature with Weighted Moving Average timeseries method and favourite product feature to better market products to prospective customers using k-Medoids clustering method.Preliminary evaluations using k-Medoids method shows two products fit to advertise by considering attributes such as sold amount, mean sold amount and transaction amount. Data evaluation using Weighted Moving Average method acquires sales forecast with Accuracy rate of 92.456%.